The Effects of Platelet-Rich-Plasma (PRP) Injection On Ligament Injury - Kloping, Yudhistira P.; Desnantyo, Andre T.; Rehatta, Nancy M. (BALI MEDICAL JOURNAL, 2016)
Background: Soft tissue injuries are becoming a problem especially among active people and athletes, thus doctors are focusing on PRP injection however variety of study results are making the beneficial effects of PRP towards soft tissue healing unclear. The purpose of this study is to clarify the effects of PRP injection on the healing aspect of a ligament injury. Methods: The experimental study used European rabbit (Oryctolagus cuniculus), which was divided into the control and treated group. The 22 samples, ankle ligaments were injured. The treated group was injected with 4 ml PRP taken autologously. On the 2nd day the samples were examined for hematoma. 4 samples from each group were also examined histopathologically. On the 2nd week, the ligament thickness of the remaining samples from each group was examined ultrasonographically. Results: The clinical result showed lower presence of hematoma on the group injected with PRP compared to the control group. The Capillary dilation was less on the treated group compared to the control group. The Inflammatory cells were less on the treated group compared to the control group. The Fibroblasts Cells was less on the treated group compared to the control group. The fibrocytes was more abundant on the treated group compared to the control group. The average of Ligament Thickness was thicker on the treated group compared to the control group. Conclusion: The Injection of PRP is beneficial to a ligament injury based on its effect on enhancing healing on the inflammation, regeneration, and remodeling phases.
Keywords: PRP, Inflammation, Healing, Ligament Injury.